Pemanfaatan Google Classroom dalam Pembelajaran Komputer dengan Menggunakan Akun Belajar.Id di SMPN 2 Jalaksana - Ginanjar, Esa; Haerudin, Dodi Ahmad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine the implementation of Google Classroom in computer learning at SMPN 2 Jalaksana through the Belajar.id account from the Ministry of Education, Culture, Research, and Technology. This platform provides a safe and effective digital learning environment for both teachers and students. This research uses research and development methods. The steps of the 4D development model consist of define, design, develop, and disseminate stages. Data in this study were collected through several techniques including observation and in-depth interviews. The qualitative data analysis technique consists of three main stages: data reduction, data display, conclusion drawing & verification, and conclusion. Based on the interview results, 60% of the 1A class students are starting to get used to digital learning using Google Classroom, especially in shaping discipline, responsibility, and digital character. However, 40% of the other students still require guidance to adapt to the rhythm of digital learning. Overall, the use of Belajar.id accounts has proven to support the effectiveness of learning and contribute to the formation of students' digital character in the era of digital education transformation.